Autocatalytic Processing and Substrate Specificity of Arabidopsis Chloroplast Glutamyl Peptidase . Issue 1 (6th July 2020) - Bhuiyan, Nazmul H.; Rowland, Elden; Friso, Giulia; Ponnala, Lalit; Michel, Elena J. S.; van Wijk, Klaas J.
Abstract : Chloroplast glutamate peptidase has physiological exo- and endo-glutamyl peptidase activity, and autocatalytic removal of its C-terminal prosequence increases substrate size limitation. Abstract: Chloroplast proteostasis is governed by a network of peptidases. As a part of this network, we show that Arabidopsis ( Arabidopsis thaliana ) chloroplast glutamyl peptidase (CGEP) is a homo-oligomeric stromal Ser-type (S9D) peptidase with both exo- and endo-peptidase activity. Arabidopsis CGEP null mutant alleles ( cgep ) had no visible phenotype but showed strong genetic interactions with stromal CLP protease system mutants, resulting in reduced growth. Loss of CGEP upregulated the chloroplast protein chaperone machinery and 70S ribosomal proteins, but other parts of the proteostasis network were unaffected. Both comparative proteomics and mRNA-based coexpression analyses strongly suggested that the function of CGEP is at least partly involved in starch metabolism regulation. Recombinant CGEP degraded peptides and proteins smaller than ∼25 kD. CGEP specifically cleaved substrates on the C-terminal side of Glu irrespective of neighboring residues, as shown using peptide libraries incubated with recombinant CGEP and mass spectrometry. CGEP was shown to undergo autocatalytic C-terminal cleavage at E946, removing 15 residues, both in vitro and in vivo. A conserved motif (A[S/T]GGG[N/G]PE946 ) immediately upstream of E946 was identified in dicotyledons, but not monocotyledons. Structural modeling suggested that C-terminal processing increases the upper substrate size limit by improving catalytic cavity access. In vivo complementation with catalytically inactive CGEP-S781R or a CGEP variant with an unprocessed C-terminus in a cgep clpr2 - 1 background was used to demonstrate the physiological importance of both CGEP peptidase activity and its autocatalytic processing. CGEP homologs of photosynthetic and nonphotosynthetic bacteria lack the C-terminal prosequence, suggesting it is a recent functional adaptation in plants.